2008
DOI: 10.1136/ard.2007.084772
|View full text |Cite
|
Sign up to set email alerts
|

EULAR evidence-based recommendations for the diagnosis of hand osteoarthritis: report of a task force of ESCISIT

Abstract: Objectives: To develop evidence-based recommendations for the diagnosis of hand osteoarthritis (OA). Methods: The multidisciplinary guideline development group, representing 15 European countries, generated 10 key propositions regarding diagnosis using a Delphi consensus approach. For each recommendation, research evidence was searched for systematically. Whenever possible, the sensitivity, specificity and likelihood ratio (LR) were calculated; relative risk and odds ratios were estimated for risk factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
283
0
20

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(306 citation statements)
references
References 87 publications
3
283
0
20
Order By: Relevance
“…On the other hand, the increment of risk rates with obesity for hip OA was not as much as knee OA (38,39). In the EULAR recommendations, obesity takes place among major risk factors for hand OA (evidence level 2a) (26). In line with existing literature, we report that obesity and morbid obesity increase the risk of developing SKO up to 5.8 times in men and women (95% CI 2.1-16.2).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…On the other hand, the increment of risk rates with obesity for hip OA was not as much as knee OA (38,39). In the EULAR recommendations, obesity takes place among major risk factors for hand OA (evidence level 2a) (26). In line with existing literature, we report that obesity and morbid obesity increase the risk of developing SKO up to 5.8 times in men and women (95% CI 2.1-16.2).…”
Section: Discussionsupporting
confidence: 74%
“…EULAR reported that SHaO was found to be rare under 40 years of age, whereas it had a dramatic increase in rate in women after their 40s. Therefore, being over 40 years old was reported (evidence level 2a ) as a major risk factor for developing SHaO in numerous studies (26). In a recent study about hip OA, it was shown that between 40-44 years of age, primary radiographical hip OA prevalence was 0.7% and increased to 14% at 85 years of age (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients had also to report pain at the thumb as their main symptom. The combination of radiological and clinical findings has been recommended for making a more accurate diagnosis of thumb CMC OA [47]. Exclusion criteria were as follows: previous treatment intervention with surgery in the hand or the forearm; corticosteroid injection or any physical therapy intervention within 6 months before the study; multiple pain diagnoses of the upper extremity, e.g., carpal tunnel syndrome, de Quervain's tenosynovitis, shoulder pathology, and cervical radiculopathy; evidence of systemic illness (rheumatoid arthritis, psoriatic arthritis, systemic lupus erythematosus); fibromyalgia syndrome; complex regional pain syndrome; any degenerative or non-degenerative neurological conditions where pain perception can be altered; presence of any symptom in the non-dominant hand; evidence of radiographic alterations at the first CMC joint in the nondominant hand; presence of a score greater than 6 points in the Beck Depression Inventory (BDI-II); or presence of a score >30 points on the State Trait Anxiety Inventory (STAI).…”
Section: Participantsmentioning
confidence: 99%
“…Diabetes mellitus (DM): Current use of medications prescribed to treat DM or fasting serum glucose levels ≥126 mg/dL (15).…”
Section: Definition Of Variablesmentioning
confidence: 99%